Molecular mapping of the human major histocompatibility complex - Dunham, I; Dunham, Ian (1988)
1. Pulsed field gel electrophoresis (PFGE) and cosmid walking have been used to establish a molecular map of the human major histocompatibility complex (MHC). Single copy hybridisation probes were isolated from clusters of cosmid clones, one containing the C2, factor B, C4 and 21-hydroxylase genes, and the other containing the genes for tumour necrosis factors (TNF) a and B. These probes and HLA class I and class II gene probes were hybridised to Southern blots of genomic DNA which had been digested with infrequently cutting restriction endonucleases and separated by PFGE. The data obtained allowed the construction of a long range genomic restriction map, indicating the MHC spans 3800 kb. This map orients the complement gene cluster with respect to DRA, the C2 gene being telomeric to the 21-hydroxylase B gene. In addition, the positions of the TNF genes were defined. The DRA and 21-hydroxylase B genes are separated by no greater than 390 kb, while the distance between the C2 and TNFA genes is 325 kb. The HLA-B locus lies about 250-300kb telomeric of the TNFB gene. 2. The long range DNA organisation of the class II and class III regions in eight HLA homozygous cell lines has been analysed using PFGE. Comparison of the size of the BssHII restriction fragment observed for these cell lines and five individuals possessing one to three C4 genes, shows that the organisation of the C4 genes on each chromosome can be deduced from a single PFGE experiment. Outside of the C4 and 21-OHase loci the class III region shows a highly invariant structure, with no detectable differences in the amount of DNA present. Moreover the class III region is rich in CpG-islands, one of which has been characterised, and contains at least thirteen new genes. However, in the class II region, two differences between common haplotypes have been found. The DRw52-related haplotypes have the same DNA organisation. DR2 haplotypes possess 20-30 kb more DNA in the DRB region. DRw53 haplotypes have 100-130 kb more DNA than DRw52-related haplotypes in the region containing the DRB and DQA genes.